Peran Literasi Digital Dalam Meningkatkan Karakter Gemar Membaca Siswa Kelas IV SD Negeri 2 Tambongwetan Tahun Pelajaran 2023/2024 - Wulan Wilanten; Nela Rofisian; Sri Suwartini (CV. ITTC INDONESIA, 2024)
This study aims to determine the role of digital literacy in improving the character of fond of reading of fourth grade students of SD Negeri 2 Tambongwetan. The research method used is descriptive qualitative, which is a research method used to examine the condition of natural objects. The data feeder technique used is triangulation. Data collection through observation, in-depth interviews with principals, homeroom teachers, parents, and students. The results of this study show that digital literacy through the use of digital books, learning videos and interactive learning applications plays an important role in increasing students' interest and character in reading. Students showed an increase in the frequency of reading, the desire to find information, and the ease of access in finding subject matter and reading resources. Digital literacy also makes the reading process more interesting and interactive, so students feel more engaged and motivated to read independently. From the results of this study, it can be concluded that digital literacy has an important role in shaping the character of fond of reading in grade IV students. Effective use of digital literacy can support an innovative learning process and increase students' interest in reading. It is hoped that these findings can be a reference for schools and teachers in developing literacy programs based on digital technology.